إعداد مواد التعليمية غناء العربية عن المفردات لطلبة مستوى متوسطة الإسلامية - Isyna Finurika; Alif Kafa Toyyibah (Kilmatuna: Journal Of Arabic Education, 2021)
Vocabulary is an important element in language, students will easily become skilled in their Qiro'ah, Kitabah, Istima 'and Kalam also because of their mastery in vocabulary, so the authors are interested in raising discussions related to the preparation of teaching materials in the form of Arabic songbooks about vocabulary in Arabic books Madrasah Tsanawiyah level, because students become helped and easy to memorize vocabulary with Arabic songs, this book will be read together every time starting learning activities with the aim of stimulating student enthusiasm at the beginning of the lesson. The research method used in this research is Research and Development (R&D) or research and development. In this study, researchers used 3 data collection techniques, namely: observation, interviews and questionnaires. In this study the researcher only tested the Arabic songbook about this vocabulary in the form of socialization. From the results of small group trials, the researcher gets the results of a questionnaire to determine the quality of the textbooks 83% (perfect), from the results of the field trials, the researcher gets the questionnaire results 79% (very good) or has a pretty good quality as a guide to memorize Arabic vocabulary. easy according to 7th grade students at Madrasah Tsanawiyah Al-Muhtadi.